KHILAFAH STATE VERSUS NATION-STATE - Basri Basri; Mohammad Takdir (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2023)
This article aims to discuss the discourses and debates on Khilafah system in Muslim countries and how it transforms into a nation-state system, specifically in Indonesia. These dicourses and debates include the contestation and trends in the connection between Islam as a religion and Indonesia as a nation-state, which reemerged after the ban of Hizbut Tahrir Indonesia (HTI) in 2017 and The Front of Islamic Defenders (Front Pembela Islam/FPI) in 2020 accordingly under President Jokowi’s administration. This article employs descriptive qualitative analysis to investigate the historical sequences of the discourses and debates on the genealogy, contestation, and relation between the Khilafah system and the nation-state system in Indonesia to uncover the fundamental ideology which underlines the conflicting interests in the debate. It operates the historical-sociological approaches to examine the data collected from books, articles, journals, and newspapers which contain the opinions of the prominent Muslim scholars gearing the dynamic discourses and debates on the nation-state system and Khilafah system. This article, therefore, attempts to demonstrate how Khilafah system idea emerged after the death of the prophet Muhammad and how this idea was contested by Muslim scholars and leaders today. This article suggests that in the struggle of ideology, thought, and movement inside the Muslim countries including Indonesia, the Khilafah system and the system of nation-state came into conflict. Further, the two forms of engagement between Islam and the nation-state are driven by nationalism.